Fishing Capacity Efficiency of Mini Purse Seine in Ternate City - Salim, Fajria Dewi; Damsiki, Nuraini A; Ahmad, Aditiyawan; Abubakar, Yuyun; Fadel, Ariyati A (Jurnal Biologi Tropis, 2024)
The level of fishing efficiency and capacity of a fishery provides a useful instrument for policymakers to design management and control the response of the fishing industry to management. For this reason, fishing efficiency and capacity measures must be applied appropriately depending on a particular fishery's management and specific characteristics (Espino et al., 2006). This study aims to determine the efficiency of fishing capacity in mini purse seine in Ternate City. This research uses a descriptive quantitative method, DEA (Data Envelopment Analysis), to measure the technical efficiency of production (fishing capacity)—efficiency analysis using Microsoft Excel supported by frontier add-ins. The mini purse seine units that became Decision Making Units (DMU) were 20 DMUs consisting of 11 DMUs in Rua village, and 9 DMUs in Moti sub-district, Ternate City. Load capacity, fishing trip, fuel volume, number of crew members, and engine capacity are input factors in this study, while average production volume is the output factor. The results showed that 13 mini purse seine business units (13 DMUs) in Ternate City were inefficient (<1) and 7 mini purse seine business units were efficient. Most of the mini purse seine fishing capacity in Ternate City showed an inefficient condition (<1). The inefficient condition is caused by the excessive use of inputs (fishing capacity). Potential improvements can be made by reducing the use of inputs to obtain maximum output. Trip catch, fuel volume, and number of crew are production inputs that can be improved for optimum output in mini purse seine fishing in Ternate City. This research contributes to understanding best practices in using mini purse seines while supporting efforts to achieve economic sustainability in the capture fisheries sector in Ternate City.